Computational fluid dynamics review 2010 - Hafez, M. M.; Ōshima, K. (Kōichi), 1927-; Kwak, Dochan (World Scientific Pub. Co., 2010)
This volume contains 25 review articles by experts which provide up-to-date information about the recent progress in computational fluid dynamics (CFD). Due to the multidisciplinary nature of CFD, it is difficult to keep up with all the important developments in related areas. CFD Review 2010 would therefore be useful to researchers by covering the state-of-the-art in this fast-developing field.